Variação sazonal e a influência da estrutura da paisagem na ocorrência de Charadriidae e Scolopacidae no litoral do Rio Grande do Sul - Scherer, Angelo Luís (Universidade do Vale do Rio do Sinos, 2010)
The coast of Rio Grande do Sul State, Brazil, includes a remarkable number of habitats used by many Nearctic shorebirds species during the non-breeding season in the austral summer months. During two years we evaluated the abundance of shorebird monthly, along 120 km of the beach in Rio Grande do Sul, southern Brazil. Of the 17 species recorded, the most abundant were the Sanderlings (Calidris alba), White-rumped Sandpiper (Calidris fuscicollis) and Red Knot (Calidris canutus). The highest abundance occurred between October and April, and the lowest abundance occurred between May and September. Of the total species, 14 were migrant shorebirds from north hemisphere, one is a migrant shorebird from south hemisphere and two were resident. Some species were present throughout the year. Nine species were constantly registered, two were sporadic and six were incidental recorded. This study confirms that the beaches of Rio Grande do Sul State, are an important migration stopover and winter site for many shorebir
Keywords: aves; migração; movimentos sazonais; ecologia; ecology; migration; non-breeding; seasonal abundance; shorebirds; abundance; Ciências Biológicas